Conclusion and recommendations - Marco Antonio ORTIZ SANCHEZ (A+BE: Architecture and the Built Environment)
This research provided insights into the comfort and energy-consuming behaviours of home occupants and into grouping these home occupants based on their individual differences. This was achieved by using a human-centered approach to an engineering challenge, by assuming comfort as a holistic experience of the home environment, and by treating the ‘occupant-environment’ interactions as a dynamic system.